Prospective cohort study of appendicectomy for treatment of therapy‐refractory ulcerative colitis. Issue 12 (8th August 2019) - Stellingwerf, M. E.; Sahami, S.; Winter, D. C.; Martin, S. T.; D'Haens, G. R.; Cullen, G.; Doherty, G. A.; Mulcahy, H.; Bemelman, W. A.; Buskens, C. J.
Abstract : Introduction: Appendicectomy may reduce relapses and need for medication in patients with ulcerative colitis, but long‐term prospective data are lacking. This study aimed to analyse the effect of appendicectomy in patients with refractory ulcerative colitis. Methods: In this prospective multicentre cohort series, all consecutive patients with refractory ulcerative colitis referred for proctocolectomy between November 2012 and June 2015 were counselled to undergo laparoscopic appendicectomy instead. The primary endpoint was clinical response (reduction of at least 3 points in the partial Mayo score) at 12 months and long‐term follow‐up. Secondary endpoints included endoscopic remission (endoscopic Mayo score of 1 or less), failure (colectomy or start of experimental medication), and changes in Inflammatory Bowel Disease Questionnaire (IBDQ) (range 32–224), EQ‐5D™ and EORTC‐QLQ‐C30‐QL scores. Results: A total of 28 patients (13 women; median age 40·5 years) underwent appendicectomy. The mean baseline IBDQ score was 127·0, the EQ‐5D™ score was 0·65, and the EORTC‐QLQ‐C30‐QL score was 41·1. At 12 months, 13 patients had a clinical response, five were in endoscopic remission, and nine required a colectomy (6 patients) or started new experimental medical therapy (3). IBDQ, EQ‐5D™ and EORTC‐QLQ‐C30‐QL scores improved to 167·1 ( P  < 0·001), 0·80 ( P  = 0·003) and 61·0 ( P  < 0·001) respectively. After a median of 3·7 (range 2·3–5·2) years, a further four patients required a colectomy (2) or new experimental medical therapy (2). Thirteen patients had a clinical response and seven were in endoscopic remission. The improvement in IBDQ, EQ‐5D™ and the EORTC‐QLQ‐C30‐QL scores remained stable over time. Conclusion: Appendicectomy resulted in a clinical response in nearly half of patients with refractory ulcerative colitis and a substantial proportion were in endoscopic remission. Elective appendicectomy should be considered before proctocolectomy in patients with therapy‐refractory ulcerative colitis. Abstract : Appendicectomy may reduce relapses and need for medication in patients with ulcerative colitis, but long‐term prospective data are lacking. In this study, appendicectomy resulted in a clinical response in 13 of 28 patients with therapy‐refractory ulcerative colitis and a substantial proportion were in endoscopic remission. Elective appendicectomy should therefore be considered before proctocolectomy in these patients. Has promise Abstract : Antecedentes: La apendicectomía puede reducir las recaídas y la necesidad de medicación en pacientes con colitis ulcerosa ( ulcerative colitis, UC), sin embargo, faltan datos a largo plazo obtenidos de forma prospectiva. El objetivo de este estudio fue analizar el efecto de la apendicectomía en pacientes con UC refractarios al tratamiento. Métodos: En esta serie prospectiva de cohortes multicéntrica, a todos los pacientes consecutivos con UC refractaria remitidos para proctocolectomía entre noviembre de 2012 y junio de 2015 se les recomendó en su lugar someterse a una apendicectomía laparoscópica. El criterio de valoración principal fue la respuesta clínica (disminución de ≥ 3 puntos del sistema de puntuación parcial de Mayo que varía de 0 a 9) a los 12 meses y en el seguimiento a largo plazo. Los criterios de valoración secundarios incluyeron la remisión endoscópica (puntuación endoscópica de Mayo ≤ 1), fracaso (colectomía o inicio de medicación experimental) y cambios en el IBDQ (rango 32‐224), EQ‐5D y EORTC‐QLQ‐C30‐QL. Resultados: En total, 28 pacientes (13 mujeres, mediana de edad 40, 5) se sometieron a una apendicectomía. El IBDQ de referencia promedio fue de 127, 0; el EQ‐5D 0, 65 y el EORTC‐QLQ‐C30‐QL 41, 1. A los 12 meses, 13 pacientes presentaban una respuesta clínica, cinco estaban en remisión endoscópica y nueve precisaron colectomía ( n = 6) o un nuevo tratamiento médico experimental ( n = 3). El IBDQ, EQ‐5D y EORTC‐QLQ‐C30‐QL mejoraron a 167, 1 ( P < 0, 001); 0, 80 ( P = 0, 003) y 61, 0 ( P < 0, 001) respectivamente. Después de una mediana de 3, 7 años (rango 2, 3‐5, 2), otros cuatro pacientes requirieron una colectomía ( n = 2) o un nuevo tratamiento médico experimental ( n = 2). Trece pacientes presentaron respuesta clínica y siete se encontraban en remisión endoscópica. La mejora del IBDQ, el EQ‐5D y el EORTC‐QLQ‐C30‐QL se mantuvo estable a lo largo del tiempo. Conclusión: La apendicectomía consiguió una respuesta clínica en casi la mitad de los pacientes con UC refractaria. La apendicectomía electiva debería ser considerada antes que la proctocolectomía en pacientes con UC refractaria al tratamiento.